Circuit Training: Model Latihan Untuk Menunjang Ketepatan Pukulan Backhand Bulutangkis - Puja Perdana Putra; Rufi'i; Abd Cholid (Journal Sport Area, 2020)
The objective of this research was to develop circuit training exercise model to increase the accuracy of backhand strokes for badminton athletes and trainers. This research was conducted by several stages which started from validation stage by instructional design expert and content expert, then designing questionnaire which was validated by content expert and sports psychology expert, testing stage to colleagues, athletes as group and wide group. This testing was carried out in Patriot Sidoarjo Badminton Federation. The instrument of this research was questionnaire from coaches’ response and athletes’ response. Those responses were analyzed by descriptive statistics. The finding shows that the results of validation from content expert and instructional design expert, testing to small group and wide group, and implementation testing were good category. It can be concluded that this model that is intended to increase backhand strokes in badminton is valid to adopted by badminton coaches.